Estudio de prefactibilidad para la instalación de una planta de producción de camisas elaboradas a base de algodón y poliéster reciclado - Chirito Saenz, Leonardo Ruben (2022)
This project consists of a study for the installation of a shirt-making plant based on cotton and recycled polyester aimed at the national market, with the main objective of demonstrating the technical, economic, financial, social, and environmental viability of the market. The product to be developed finds its differentiating factor in its raw material, since it takes advantage of plastic waste to generate a new input, PET recycled plastic fibers. With this fabric you can make garments of the same quality as others that do not contribute to reducing pollution caused by plastic waste. As a result of the market study, the demand for the project will increase to 153 909 cotton shirts with recycled polyester by 2025. Considering a male public target belonging to Metropolitan Lima, from 13 to 55 years old, from NSE B and C. which represents a market share of 6,28%. Plant size is defined by market size. The project will have an 800 m2 plant, a plant capacity of 264 943 and a production of 153 909 recycled cotton and polyester shirts, which will be in the district of Lurín within the “Macropolis” industrial park. For Chapter VI of Organization and Administration, the legal entity, Closed Stock Company (S.A.C.), is determined. A total investment of S/ 926 644 was obtained, made up of financing through the Banco de Credito del Peru of 40% for 5 years. An economic and financial NPV of S/ 1 030 125 and S/ 1 066 411, respectively, and an IRR of 44,64% and 59,98%, respectively, were obtained. Finally, an added value will be highlighted for the 5 years of the project of S/ 8 301 440 and 37 jobs, it is concluded that the project has a positive impact on society.